Resting vagal activity in schizophrenia: meta-analysis of heart rate variability as a potential endophenotype - Clamor, Annika; Lincoln, Tania M.; Thayer, Julian F.; Koenig, Julian (The British journal of psychiatry, 2016)
Background - Cardiac vagal tone, indexed by heart rate variability (HRV), is a proxy - for the functional integrity of feedback mechanisms integrating central - and peripheral physiology. Aims - To quantify differences in HRV in individuals with schizophrenia compared - with healthy controls. Method - Databases were systematically searched for studies eligible for - inclusion. Random effect meta-analyses of standardised mean differences - were calculated for vagal activity indicated by high-frequency HRV and - the root mean square of successive R-R interval differences (RMSSD). Results - Thirty-four studies were included. Significant main effects were found - for high-frequency HRV (P = 0.0008; Hedges' - g =-0.98, 95% CI −1.56 to −0.41, k = - 29) and RMSSD (P<0.0001; g =-0.91, - 95% CI −1.19 to −0.62, k = 24), indicating lower vagal - activity in individuals with schizophrenia than in healthy controls. - Considerable heterogeneity was evident but effects were robust in - subsequent sensitivity analyses. Conclusions - Given the association between low HRV, threat processing, emotion - regulation and executive functioning, reduced vagal tone may be an - endophenotype for the development of psychotic symptoms.
accepted 19 Feb 2015
Gesehen am 04.05.2020